Is faecal calprotectin useful in the screening of inflammatory bowel disease in children? - a three year review of practice. (24th May 2012) - Gaynor, E; Howarth, L; Kammermeier, J; Sullivan, P; Rodrigues, A
Abstract : Aims: Calprotectin is a neutrophil intracellular calcium and zinc binding protein that has been shown to be associated with intraluminal intestinal inflammation when detected in stool. Its use as a non-invasive marker of inflammatory bowel disease (IBD) is well validated in children and adults. Levels of faecal calprotectin (FC) >60 μg/g is considered abnormal, however a FC >100 μg/g has a sensitivity of 98% and specificity of 91% in detecting children with IBD. The authors carried out a study to evaluate the current use of FC as screening tool for IBD, in a tertiary paediatric gastroenterology unit. Methods: All FC requests sent over a 3 year period between January 2008 and February 2011 in children aged 1 to 16 years of age (n=68) were reviewed. Additionally clinical notes were analysed for indication for testing, clinical impression on first consultation and subsequent change in management following FC result. Results: Of the 68 FC requests, 47 were in children suspected to have inflammatory bowel disease, 7 were used to monitor known inflammatory bowel disease and 14 were for other indications. FC was >100 μg/g in 23 of 68 children (30%). Of the 47 children with suspected IBD at referral, 35 (74%) had normal FC and did not subsequently undergo an endoscopy. 4 children with FC<100 μg/g underwent endoscopy – all of which were normal. There were no known false negative outcomes at the time of abstract submission. 5 children with suspected IBD with a FC>100 μg/g had abnormal endoscopy. 1 child with a FC>100 μg/g, had no endoscopy as campylobacter was isolated through stool culture, and responded well to treatment. There were however 2 children with elevated FC, but with normal histology following endoscopy. Conclusion: Review of our practice over the last 3 years has demonstrated that when FC was measured ie when IBD was possible but children seemed clinically well, IBD was only diagnosed in those with a raised FC. During the study period no child with symptoms consistent with IBD, with a normal FC was subsequently diagnosed with IBD. In well children a normal FC could reduce the need for diagnostic endoscopy. FC is a useful additional screening tool.